ANALISIS TINDAK TUTUR PRAGMATIK GURU TERHADAP SISWA PELANGGAR TATA TERTIB SEKOLAH DI SMP NEGERI 27 MAKASSAR - Nurul Sri Wahyuni; Nurhusna; Asri Ismail (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Nurul Sri Wahyuni, 2026. “Analysis of Teachers’ Pragmatic Speech Acts towards Students Who Violate the Regulations of SMP Negeri 27 Makassar”. This study aims to describe the pragmatic forms and functions of speech acts used by teachers in handling students who violate school rules at SMP Negeri 27 Makassar. A qualitative descriptive method was used, with data collected through observation, recording, and direct note-taking of teacher-student interactions in the school environment. The results indicate that the most dominant speech acts used by teachers are directives, primarily commands, prohibitions, demands, and advice, aimed at regulating student behavior to comply with school norms. Representative, expressive, commissive, and declarative speech acts were also found, functioning to reprimand, explain the reasons behind rules, provide affirmation, and demonstrate the teacher’s institutional authority in fostering student discipline. These findings indicate that teachers’ language plays a crucial role as a tool for social control, character development, and enforcement of school rules through communication strategies oriented toward discipline and education.